Comparison of Dentin Tensile Strength of Impacted Teeth Versus Erupted Teeth: A Comparative Analytical Study - Srivarsan Ravi; Dr. Dinesh Kumar (Revista Electronica de Veterinaria, 2024)
Objectives:Dentin provides the primary structural foundation of the human tooth, playing a critical role in distributing masticatory forces and supporting the overlying enamel. This in vitro study aimed to evaluate and compare the ultimate dentin tensile strength of completely impacted human teeth versus fully erupted functional teeth. Materials and Methods:Sound human erupted teeth and completely impacted teeth were collected following extraction for clinical indications. The specimens were sectioned to isolate standardized dentin blocks, ensuring the exclusion of enamel and pulpal soft tissues. Tensile strength evaluation was carried out using a specialized multi-test universal testing device. Uniaxial tensile load was applied at a constant crosshead speed until specimen failure occurred. Continuous data recording captured the maximum force (N), tensile stress at tensile strength (MPa), tensile strain at break (%), and ultimate tensile stress at break (MPa) for both cohorts. Results:The ultimate tensile stress at break for the dentin of impacted teeth was found to be 6.21 MPa, which was substantially higher than that of erupted teeth, which demonstrated a tensile stress at break of 2.79 MPa. Impacted teeth also exhibited a higher maximum force tolerance (71.68 N) compared to erupted teeth (31.50 N). Furthermore, the tensile stress at tensile strength reached 9.62 MPa for impacted dentin compared to 4.50 MPa for erupted dentin, while the tensile strain at break was 4.55% and 0.84%, respectively. Conclusion:The dentin of completely impacted teeth possesses significantly superior tensile strength and strain capacity compared to the dentin of erupted teeth. These findings indicate that exposure to the oral environment, physiological aging, and functional masticatory loading significantly alter the mechanical properties and resilience of dentin substrates.